The application of elastin-like peptides in cancer, tissue engineering and ocular disease - Dabo Jiang; Yang Yang; Xiuyi Yang; Boxuan Wang; Wenxuan Fan; Yuchen Liu; Xiaofei Xin; Lifang Yin (Elsevier, 2023)
Elastin-like polypeptides (ELPs) are macromolecular biopolymers composed of natural amino acids. ELPs can be prepared by genetic engineering so that their amino acid sequences and molecular weight can be precisely manipulated. Moreover, therapeutic peptides and pharmacological agents can be inserted into the sequences by genetically encoded design. ELPs also have a special thermal response behavior and exhibit a reversible phase transition with temperature changes, which can be fully preserved when they are coupled with other small-molecule drugs or peptides. In addition, it has good biological properties such as good biocompatibility and low immunogenicity. Based on the above characteristics, ELPs have been widely studied in the field of biomedical engineering like drug delivery and tissue engineering. This paper briefly summarizes the application and challenges of ELPs in tumor treatment, tissue engineering, and ocular delivery.